2014
DOI: 10.1007/s00426-014-0543-y
|View full text |Cite
|
Sign up to set email alerts
|

Map learning and the alignment effect in young and older adults: how do they gain from having a map available while performing pointing tasks?

Abstract: Two studies were conducted to investigate age-related differences between young and older adults in the impact of a map being available or not while performing aligned and counter-aligned pointing tasks. In the first study, 19 young adults (aged 20-30) and 19 young-old adults (aged 65-74) studied a map and performed a pointing task. In the second, three groups of adults, 19 of them young (aged 20-30), 19 young-old (aged 65-74), and 19 old-old (aged 75-84), studied a map and performed a pointing task, first wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
34
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 46 publications
3
34
1
Order By: Relevance
“…As Jansen and Heil [33] have determined, in the aging process, important cognitive functions, such as visuo-spatial abilities and working memory may be impaired. On the other hand, in contrast to Borella et al, [21] we did not find significant differences between age groups in the number of opposite responses. Opposite responses (four points of deviation in our scoring) were not frequent answers in any age group.…”
Section: Discussioncontrasting
confidence: 84%
See 3 more Smart Citations
“…As Jansen and Heil [33] have determined, in the aging process, important cognitive functions, such as visuo-spatial abilities and working memory may be impaired. On the other hand, in contrast to Borella et al, [21] we did not find significant differences between age groups in the number of opposite responses. Opposite responses (four points of deviation in our scoring) were not frequent answers in any age group.…”
Section: Discussioncontrasting
confidence: 84%
“…Nevertheless, it is noteworthy that the group 9 gender interaction did not show significant differences. Other recent studies, using the PPT, have also indicated similar gender differences across age groups [21,30].…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Mixed results have been found for age effects when learning locations from maps and small-scale arrays not requiring physical movement to explore. While some have found clear evidence of spatial decline (Iachini et al, 2009; Kirasic, 2000; Moffat & Resnick, 2002), others have shown preservation when memory prompts are present (Yamamoto & DeGirolamo, 2015) or a mix of preservation and decline depending on alignment of perspective (Borella, Meneghetti, Muffato, & De Beni, 2015). The encoding and retention of spatial layouts by older adults clearly merits further examination, as in the present studies.…”
Section: Introductionmentioning
confidence: 99%